Functional Dynamics of Arginine Mono- and Di-Methylation - Xi’ang Wang; Bin Zhu; Robert Winn; Shanfa Lu; Hengbin Wang (Cells)
Arginine methylation is a crucial post-translational modification (PTM) that plays a significant role in various biological processes. It occurs in two primary forms: mono-methylation (MMA) and di-methylation (DMA), with the latter further classified into symmetric (SDMA) and asymmetric methylation (ADMA). This review examines the functional implications of these methylation states, current detection methodologies, proteomics-based analytical approaches, and the different impacts of these methylations on protein function. Finally, the role of protein arginine methyltransferases (PRMTs) and their substrate specificity in shaping the arginine methylome are discussed.